Shooting to kill: the ethics of police and military use of lethal force - Miller, Seumas (Oxford University Press, 2016)
Introduction -- Morally permissible use of lethal force: a taxonomy -- Killing in self-defence -- Police officers, regular soldiers and normative institutional analysis -- Police use of lethal force -- Police use of lethal force and suicide bombers -- Military use of lethal force -- Civilian immunity -- Humanitarian armed intervention -- Targeted killing -- Autonomous weapons and moral responsibility -- Conclusion